PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA DIVISI PASANG BARU PT. TELKOM AKSES PEKANBARU - Yapentra, Arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
ABSTRACT Â : This study aims to determine the influence of leadership on employee performance at the new tide division of PT. Telkom Access Pekanbaru. With a total of 34 respondents. In analyzing the data obtained from the object of this study using the Simple Linear Regression Analysis Method, it can be concluded that there is a significant influence of leadership variables on employee performance in the new tide division of PT. Telkom Access Pekanbaru. This means that employee performance is strongly influenced by the leadership given. The results of the validation test, reliability test and normality test of all items were declared valid because Rhitung> Rtabel. The results of this study are the Simple Linear Regression Equation model Y = 3.031 + 0.923X. Based on the data in the t test where t count 13.534> t table 2.039 means that there is a significant influence between leadership on employee performance in the new tide division. And the test results of the coefficient of determination (R2) = 0.851 (85.1%) while the side (100% - 85.1% = 14.9%) is influenced by other variables outside the study.